Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1093/pcp/pcf181
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Sterols and Triterpenes in Cell Suspension Cultures of Uncaria tomentosa

Abstract: ;Pectin administered to Uncaria tomentosa cell suspension cultures, was found to increase the production of triterpene acids (ursolic and oleanolic acid), however, neither growth nor sterol accumulation were affected. Cell cultures showed that pectin treatment caused a rapid threefold increase in the activities of enzymes involved in the biosynthesis of C 5 and C 30 isoprenoid, such as isopentenyl diphosphate isomerase and squalene synthase. The activity of a farnesyl diphosphatase, which could divert the flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 51 publications
3
43
0
1
Order By: Relevance
“…Elicitation with citrus pectin, as previously reported (Flores-Sa´nchez et al 2002), did not provoke changes in the growth characteristics of U. tomentosa cell cultures.…”
Section: Elicitation Responsesupporting
confidence: 83%
See 2 more Smart Citations
“…Elicitation with citrus pectin, as previously reported (Flores-Sa´nchez et al 2002), did not provoke changes in the growth characteristics of U. tomentosa cell cultures.…”
Section: Elicitation Responsesupporting
confidence: 83%
“…The extracts were evaporated under vacuum, dissolved in 0.5 ml methanol, and analysed by HPLC and TLC as previously described (Flores-Sa´nchez 2002). Ursolic and oleanolic acids, from 40 mg extract, were purified by TLC and analysed by 1 H NMR on a 300 MHz Varian Mercury spectrometer, measuring the methyl signal integrals at d 1.14 for oleanolic acid and d 1.08 for ursolic acid in CDCl 3 with tetramethylsilane as reference.…”
Section: Triterpene Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar result was obtained in P. ginseng overexpressing SS (PgSS1) gene (Lee et al 2004). It has been suggested that active biosynthesis of triterpenes occurs when sterol formation has been sacrificed (Flores-Sánchez et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Pectin suspensions from Citrus fruits (87% galacturonic acid and 8.7% methoxy groups, Sigma) were prepared according to the method of Flores-Sanchez et al (2002).…”
Section: Elicitationmentioning
confidence: 99%